Co-producing Future Earth: ambiguity and experimentation in the governance of global environmental change research - Hadley Kershaw, Eleanor (2018)
The aim of this thesis is to investigate efforts to transform global environmental change research through co-design and co-production (involving non-academic actors in research governance and conduct). Social scientific work to date on this topic has largely taken an evaluative perspective, outlining challenges of and guidelines for co-production on the ground. By contrast, there is little work on how co-production is conceptualised and put into practice through (international) research governance. Yet institutions aiming to govern research are significant arbiters of meaning and power; their efforts to change research are worthy of investigation.